An overview of pavement maintenance management strategies in Malaysia - Azlina, Ismail; Intan Suhana, Mohd Razelan; Lydia, Mohd Yusof; Adnan, Zulkiple; Khairil Azman, Masri (IOP Publishing Ltd, 2021)
Pavement damages are always associated with its optimum function and considered among the main contributing factors to fatal accident. With significance growth of vehicular road traffic and of accompanying problems of overloading vehicles in Malaysia will indirectly contributed to worsen the condition. Unceasingly, road pavement will experience failures more rapidly than expected hence lead to negative socioeconomic effects. A proper and timely maintenance by road authorities must be made in order to sustain and maintain the roadway condition to keep them serviceable so that it will benefit not only safety but also improve economic growth and social development. Hence, this study was carried out to explore current practise of pavement maintenance strategies in Malaysia. To achieve that objective, a qualitative data of questionnaires distribution to industry practitioners that are involved in managing roads are analyzed to indicate the viability and practicability of pavement maintenance strategies in Malaysia. Other than that, specifics issue pertinent to pavement management also identified. The findings of this study are valuable in developing the realistic performance criteria for seamless road pavement maintenance strategies.